Effect of Intangible Investment on Non-Financial Performance of the Food and Beverage Sector in Indonesia During the Covid-19 Pandemic - Kevin Berutu; Farah Margaretha Leon (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
This study is created to know if intangible investment affect non-financial performance in food and beverage industry in Indonesia during Covid-19 pandemic from 2017 to 2021. The data used in this study were obtained from financial statements of manufacturing companies that move in food and beverage industry and consistently the annual report listed in Indonesia Stock Exchange from 2017 to 2021. This study used purposive sampling which is why the sample used in this study amounted to 100 samples. This study also use multiple linear regression models to test the hypothesis. The result of this study had proven that market capitalization and leverage have an influence on non-financial performance. While the other independent variables do not have an influence on non-financial performance.